How would citizens react to official advice in a nuclear emergency? Insights from research in three European countries. (3rd October 2020) - Turcanu, Catrinel; Sala, Roser; Perko, Tanja; Abelshausen, Bieke; Oltra, Christian; Tomkiv, Yevgeniya; Oughton, Deborah; Liland, Astrid; Zeleznik, Nadja
Abstract: Nuclear emergencies confront decision‐makers, emergency actors and publics with several challenges, many of which are related to social, ethical and communication aspects. Based on empirical data from three European countries, this paper investigates citizens' potential behaviour in an emergency situation. It analyses relationships between self‐assessed compliance with protective actions and a number of variables, including knowledge about protective actions, trustworthiness of communicators, perceived social norm (expectation of other residents' behaviour), perceived effectiveness and perceived difficulty of protective actions. Results suggest that most respondents expect to follow actions advised by authorities, except for leaving children at school or avoiding the use of phones. Moreover, large fractions of local and wider publics may seek to avoid risks by rejecting food produced in affected areas even when it satisfies legal norms or taking iodine tablets when not needed. Self‐assessed compliance with protective actions is positively correlated with perceived social norm, perceived effectiveness and compliance with other actions; and negatively correlated with perceived difficulty. Higher trust in the regulator is associated with higher compliance with some actions, but mostly among the local populations. We argue that clarifying and anticipating societal concerns contributes to enhancing societal resilience and the response to nuclear accidents.